Epigenetic Reprogramming of Cortical Neurons through Alteration of Dopaminergic Circuits - Brami-Cherrier, Karen (2014)
Alterations of the dopaminergic system are associated with the cognitive and functional dysfunctions that characterize complex neuropsychiatric disorders. We modeled a dysfunctional dopaminergic system using mice with targeted ablation of dopamine (DA) D2 autoreceptors in mesencephalic dopaminergic neurons. Loss of D2 autoreceptors abolishes D2-mediated control of DA synthesis and release. Here we show that this mutation leads to a profound alteration of the genomic landscape of neurons receiving dopaminergic afferents at distal sites, specifically in the prefrontal cortex. Indeed, we observed a remarkable down-regulation of gene expression in this area of ∼ 2,000 genes, which involves a widespread increase in the histone repressive mark H3K9me2/3. This reprogramming process is coupled to psychotic-like behaviors in the mutant mice. Importantly, chronic treatment with a DA agonist can revert the genomic phenotype. Thus, cortical neurons undergo a profound epigenetic reprogramming in response to dysfunctional D2 autoreceptor signaling leading to altered DA levels, a process that may underlie a number of neuropsychiatric disorders.